Analisis Perilaku Konsumen Usia Muda di Kota Bogor dalam Mengonsumsi Susu dan Produk Olahannya di Masa Pandemi Covid 19 - N. H. Rachmani; A. Apriantini; L. Cyrilla E. N. S. D (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
During the COVID-19 pandemic, people are started to consume foods that are highly nutritious to increased their immunity, one of them is by consuming milk and its processed products like kefir, yogurt. Milk is one of the foods favored by the community because it is rich in health benefits. The demand for this product is also increased every year. Consumer behavior was always changing along with consumer needs that follow the conditions and developments of the times. Consumers will choose products with good quality and ful fill what their needs, as well as dairy products. This study aims to analyze consumer decisions in consuming milk and its processed products in the Bogor city area during the covid 19 pandemic. The research was carried out with the stages of determining respondents, identify factors that influence consumer behavior, collecting and analyzing data. Respondents are people who live in Bogor City with an age range of 20 to 30 years purposively as many as 108 respondents. Data processing and analysis was carried out using the Spearman rank correlation test to determine the relationship between knowledge and situational variables on the decision to consume milk and its processed products. The results showed that the level of knowledge and situational had a significant and direct relationship with consumer decisions (P<0.01). This shows that the higher level of consumer knowledge of products with supportive conditions, the consumer’s decision to consume milk and its processed products is also getting stronger.